Differences in Language Proficiency and Learning Strategies Among Immigrant Women to Canada. Issue 1 (2nd January 2018) - Adamuti-Trache, Maria; Anisef, Paul; Sweet, Robert
ABSTRACT: Immigrant women to Canada face unique challenges in gaining mastery of English or French, the country's two official languages. The study focuses on differences among women with respect to pre-migration and post-migration characteristics that position them differently with respect to language learning in the social contexts where they assert their immigrant identity. This study examines issues in language acquisition among adult immigrant women and their strategies to improve language skills within four years of arrival, using nationally representative data from the Longitudinal Survey of Immigrants to Canada (LSIC). The study shows that older women, less educated women, and some immigration class groups (i.e., spouse/dependents, family class, refugees) have lower language proficiency at arrival and less chances to improve. Since immigrant women represent a heterogeneous group in terms of pre-migration language skills and access to language learning, adequate language learning support is required to facilitate their effective integration in the Canadian society.